Diagnostic delay of associated interstitial lung disease increases mortality in rheumatoid arthritis - Esteban Cano-Jiménez; Tomás Vázquez Rodríguez; Irene Martín-Robles; Diego Castillo Villegas; Javier Juan García; Elena Bollo de Miguel; Alejandro Robles-Pérez; Marta Ferrer Galván; Cecilia Mouronte Roibas; Susana Herrera Lara; Guadalupe Bermudo; Marta García Moyano; et al. (Scientific Reports, 2021)
Abstract Rheumatoid arthritis (RA) is a systemic autoimmune disease whose main extra-articular organ affected is the lung, sometimes in the form of diffuse interstitial lung disease (ILD) and conditions the prognosis. A multicenter, observational, descriptive and cross-sectional study of consecutive patients diagnosed with RA-ILD. Demographic, analytical, respiratory functional and evolution characteristics were analyzed to evaluate the predictors of progression and mortality. 106 patients were included. The multivariate analysis showed that the diagnostic delay was an independent predictor of mortality (HR 1.11, CI 1.01–1.23, p = 0.035). Also, age (HR 1.33, 95% CI 1.09–1.62, p = 0.0045), DLCO (%) (HR 0.85, 95% CI 0.73–0.98, p = 0.0246), and final SatO2 (%) in the 6MWT (HR 0.62, 95% CI 0.39–0.99, p = 0.0465) were independent predictor variables of mortality, as well as GAP index (HR 4.65, 95% CI 1.59–13.54, p = 0.0051) and CPI index (HR 1.12, 95% CI 1.03–1.22, p = 0.0092). The withdrawal of MTX or LFN after ILD diagnosis was associated with disease progression in the COX analysis (HR 2.18, 95% CI 1.14–4.18, p = 0.019). This is the first study that highlights the diagnostic delay in RA-ILD is associated with an increased mortality just like happens in IPF.